Differences of The Effect of Aerobic Sports on Cognitive Function Between Smoking and Non-Smoking Students at Daya Utama SMA, Bekasi 2017 - Devi Fitriyastanti (Publikasi Indonesia, 2022)
In Indonesia, there are 20% of adolescents aged 13-15 years who smoke. The results of a survey conducted by Global Youth Tobacco in 2009 revealed that three out of ten children aged 13-15 years in Indonesia (30.4%) already smoked, and (19.4%) started smoking at the age of 10 years. Based on data from the 2017 Daya Utama High School counseling vulnerability map, it is known that of the 216 male students in Class X – XII, 35 of them have smoking cases in the school environment, and have academic achievements that are less than the KKM, for this reason, it is necessary to think about efforts to improve the cognitive function of students so that academic achievement can be improved. One of these efforts is exercising. The purpose of this study is to provide preventive and coaching efforts to adolescents to avoid smoking and increase physical/sports activity. The technique of assessing students' cognitive abilities uses the Backward Forward Digit Span method, which is to assess short-term memory for 3 days with methods test and posttest. Research results Based on the results of the T test on smokers and non-smokers for 3 measurements, pre-test and post-test, the statistical test results obtained a Pvalue = 0.000, meaning that at 5% alpha it can be concluded that there is a significant difference between pre- and post-test cognitions. on smoking students and non-smoking students in the first, second and third day measurements. From the results of this study, it is recommended that the smoking ban continue to be enforced and pursued because the impact of smoking is not only physically damaging to the body but also reduces cognitive abilities, which will also affect learning achievement.